2020
DOI: 10.1080/02827581.2020.1813798
|View full text |Cite
|
Sign up to set email alerts
|

Finnish young adults’ perceptions of the health, well-being and sustainability of wooden interior materials

Abstract: Wood as a renewable construction material presents positive human health, well-being and sustainability-related features. Several studies have indicated its lower carbon footprint compared to the main alternative construction materials and its physiological and psychological characteristics have positive impacts on human health. The objective of this study is to investigate how young adults perceive the health, well-being and sustainability impacts of wooden interior materials. The findings from the four focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…According to the responses, it was observed that while the positive attitude was generally preserved in the age groups, “positive” attitude was replaced by “partially positive” in the older age groups. This may be because young people have a generally positive appreciation of wood for its health and sustainability impacts in the housing context [ 67 , 68 ]. Moreover, the fact that higher age can deter people from investing in activities due to shorter lifespans, health problems, diminishing abilities, and financial constraints may have contributed to this attitude [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the responses, it was observed that while the positive attitude was generally preserved in the age groups, “positive” attitude was replaced by “partially positive” in the older age groups. This may be because young people have a generally positive appreciation of wood for its health and sustainability impacts in the housing context [ 67 , 68 ]. Moreover, the fact that higher age can deter people from investing in activities due to shorter lifespans, health problems, diminishing abilities, and financial constraints may have contributed to this attitude [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were common wishes, such as more wood as a visible surface material inside the building, and a wish for more timber apartment buildings among participants of the 1998-1999 and 2017 surveys. This might be a strong indicator that the positive perception towards the use of timber as a construction material in Finland, especially in the residential market, continues today, e.g., [31,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental aspects, such as lowered carbon emissions, were only rarely mentioned as a benefit of wood materials, but sustainability can e.g. be considered to include requirements on the quality, durability, and longevity of the building (see also Häyrinen et al 2020). These benefits and requirements should be taken into consideration when increasing the knowledge and acceptance concerning WMC, both among construction industry professionals and end-users of the buildings.…”
Section: Discussion and Conclusion Contribution And Implicationsmentioning
confidence: 99%